2000
DOI: 10.1093/intqhc/12.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Quality and continuity of care in Dutch nurse clinics for people with rheumatic diseases

Abstract: Objective. Recently a new form of nurse clinic for people with rheumatic diseases has been introduced into Dutch health care. This study gives insight into: (i) patients' perceptions about the quality and continuity of care given at these (transmural) nurse clinics; and (ii) specialized rheumatology nurses' and rheumatologists' perceptions about the quality and continuity of care in the clinics.Design. Validated measurement tools (QUOTE and QCC) were used, before and after patients visited a clinic, to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 7 publications
2
23
0
Order By: Relevance
“…Patients valued nurses' communication skills and nursing care in terms of advice to use assistive devices, referral to other members of the multidisciplinary team and education 26 27. Quality and continuity of care in nurse-led clinics were perceived as good 28. Holistic care and patient-centred information were found to contribute to patient satisfaction 29…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients valued nurses' communication skills and nursing care in terms of advice to use assistive devices, referral to other members of the multidisciplinary team and education 26 27. Quality and continuity of care in nurse-led clinics were perceived as good 28. Holistic care and patient-centred information were found to contribute to patient satisfaction 29…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative studies provide important insight in patients' individual needs, functional limitations and the extent to which different types of care meet those needs,78 all of which may improve quality of care 21 28 79. However, these studies are rated with a lower level of evidence than RCTs, and subsequently, there is a high risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the studies ( n = 19, 53%) reported evaluation of organization of delivery of care, and patient satisfaction was a component of this evaluation [5,25,29,30,34,35,37–46,49–51]. Eight studies were at least partly concerned to develop a measurement method or a tool [6,7,22,31,32,35,37,51].…”
Section: Resultsmentioning
confidence: 99%
“…8 Interpersonal continuity has been studied in patients with specific chronic conditions and found to be important to parents of children with cleft lip and palate, 26 asthma, 28 and to patients with rheumatic diseases. 30 Other studies have found that the majority of patients state a preference for their regular doctor for potentially chronic conditions such as back pain, 11,31 seasonal allergies, and depression. 11 Patients with chronic illness were found to value regular visits with their physician to check the progression of their disease.…”
Section: Chronic Conditionsmentioning
confidence: 99%
“…32 Besides interpersonal continuity, chronic disease patients seem to value the transfer of their medical information between providers, which has been termed informational continuity. 9 Chronic disease patients appreciate informational continuity in the situations involving transfer of care between nurse and physician, 30 hospitalization, 32 and outpatient care teams. 7 They report that this transfer of information saves them time by not having to repeat information.…”
Section: Chronic Conditionsmentioning
confidence: 99%